Stakeholder perspectives on short-stay joint replacement programs: results from a national cross-sectional study - Ilana N Ackerman; Danielle Berkovic; Sze-Ee Soh; Justine Naylor; Peter Lewis; Richard de Steiger; Rachelle Buchbinder; Zanfina Ademi; Patrick Vallance; Ian A Harris (BMC Health Services Research, 2023)
Abstract Background The capacity to meet anticipated growth in joint replacement demand requires safe, efficient models of care. While short-stay joint replacement programs are being used internationally, they have not been widely implemented in many countries. Importantly, the critical challenges that need to be addressed ahead of large-scale program implementation remain unclear. This study aimed to investigate stakeholder perspectives on short-stay joint replacement programs, including perceived barriers and enablers to implementation and sustainability, and understand current practices in Australia. Methods Four key stakeholder groups were invited to participate in this national study: (1) health professionals who provide joint replacement care; (2) hospital administrators involved in joint replacement provision; (3) patients with recent joint replacement; and (4) carers of people with recent joint replacement. Data on perceived feasibility (0 (not at all feasible) − 10 (highly feasible), appeal (0 (not at all appealing) − 10 (highly appealing), current practices, and barriers and enablers were collected using visual analogue scales, multiple response option and open-ended questions, via an online platform. Descriptive analysis and free-text content analysis was undertaken. Results Data were available from 1,445 participants including 360 health professionals, 20 hospital administrators, 1,034 patients, and 31 carers. Short-stay program implementation was considered moderately feasible by health professionals (median 6, interquartile range (IQR) 3–8) and hospital administrators (median 5, IQR 5–6). Short-stay programs were moderately appealing to patients (median 7, IQR 2–9) but of little appeal to carers (median 3, IQR 1–7). Prominent implementation barriers included perceived limited appropriateness of short-stay programs, inadequate home supports, and issues around reimbursement models or program funding. Not having daily physiotherapy access and concerns about pain and mobility at home were common barriers for patients. Concern about patients’ ability to manage daily activities was the most common barrier for carers. Access to post-discharge services, better funding models, improved staffing, and consistent protocols and national care standards were prominent enablers. Conclusions This national study has uniquely captured multiple stakeholder perspectives on short-stay joint replacement programs. The findings can guide future quality improvement and implementation initiatives and the development of resources to best support patients, carers, clinicians, and hospitals.